Identifikasi Hama pada Komoditas Jagung selama Penyimpanan di Kabupaten Sidenreng Rappang - Rahmiyati, Rahmiyati; Sayang, Yulis; Mustaka, Zulfitriany (PLANTKLOPEDIA: Jurnal Sains dan Teknologi Pertanian, 2026)
Storage pest attacks represent a significant factor in the decline in the quality and quantity of corn kernels during storage. The objective of this study is to ascertain the species of storage pests that have been identified in corn commodities during storage in Sidenreng Rappang Regency. The study was conducted in five storage warehouses, with six sampling points in each warehouse. A total of 1 kg was collected at each sampling point. The identification of the corn samples was conducted through a series of morphological assessments. This process involved the utilisation of a laboratory sieve, a stereo microscope, and a warehouse pest identification key. The results of the study demonstrated the presence of eight pest species, namely Sitophilus sp., Tribolium castaneum, Cryptolestes ferrugineus, Rhizopertha dominica, Carpophilus dimidiatus, Palorus depressus, Alphitobius diaperinus, and Typhaea stercorea. The presence of primary pests, such as Sitophilus sp. and R. dominica, indicates the potential for internal damage to the kernels, while the dominance of secondary pests leads to storage quality degradation due to contamination and surface damage. The identification results obtained are of paramount importance in formulating a warehouse pest control strategy for the corn storage system in Sidenreng Rappang Regency.